A Novel Angiotensin I-Converting Enzyme Inhibitory Peptide Derived From Goat Milk Casein Hydrolysate Modulates Angiotensin II-Stimulated Effects on Vascular Smooth Muscle Cells - Qiao, Zijiao; Wang, Jiaqi; He, Zeqi; Pan, Lina; Feng, Konglong; Peng, Xiaoyu; Lin, Qianru; Gao, Yu; Song, Mingyue; Cao, Sufang; Chen, Yunjiao; Cao, Yong; et al. (Frontiers in Nutrition, 2022)
Hypertension is a major risk factor leading to cardiovascular disease, and is frequently treated with angiotensin I-converting enzyme (ACE) inhibitory peptides. The objective of this study was to separate and identify an ACE-inhibitory peptide from goat milk casein hydrolysates, and to evaluate its potential for improving angiotensin Ⅱ (Ang Ⅱ)-mediated adverse effects on vascular smooth muscle cells (VSMCs). A novel ACE-inhibitory peptide with the highest activity from the goat milk casein hydrolysates as determined by four steps of RP-HPLC was purified and identified as Phe-Pro-Gln-Tyr-Leu-Gln-Tyr-Pro-Tyr (FPQYLQYPY). The results of inhibitory kinetics studies indicated that the peptide was a noncompetitive inhibitor against ACE. Gastrointestinal digest in vitro analysis showed that the hydrolysate of FPQYLQYPY was still active after digestion with gastrointestinal proteases. Moreover, we found that the peptide could significantly inhibit the proliferation and migration of Ang Ⅱ-stimulated VSMCs. Further transcriptomic analysis revealed that differentially expressed genes (DEGs) were enriched in the cardiovascular disease-related pathways, and that the peptide may have the ability to regulate vascular remodeling. Our findings indicate the potential anti-hypertensive effects of FPQYLQYPY, as well implicate its role in regulating vascular dysfunction.